2021
DOI: 10.3389/fcell.2021.656795
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal Distending Toxin Promotes Replicative Stress Leading to Genetic Instability Transmitted to Daughter Cells

Abstract: The cytolethal distending toxin (CDT) is produced by several Gram-negative pathogenic bacteria. In addition to inflammation, experimental evidences are in favor of a protumoral role of CDT-harboring bacteria such as Escherichia coli, Campylobacter jejuni, or Helicobacter hepaticus. CDT may contribute to cell transformation in vitro and carcinogenesis in mice models, through the genotoxic action of CdtB catalytic subunit. Here, we investigate the mechanism of action by which CDT leads to genetic instability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…It can contribute to carcinogenesis by inducing genetic instability in replicating epithelial stem cells, which is then passed on daughter cells. Moreover, it induces senescence in CD4 + T cells, reducing the efficiency of the immune system’s anticancer response (He et al 2019 ; Mathiasen et al 2021 ; Tremblay et al 2021 ).…”
Section: Microbes Drive Hallmarks Of Cancermentioning
confidence: 99%
“…It can contribute to carcinogenesis by inducing genetic instability in replicating epithelial stem cells, which is then passed on daughter cells. Moreover, it induces senescence in CD4 + T cells, reducing the efficiency of the immune system’s anticancer response (He et al 2019 ; Mathiasen et al 2021 ; Tremblay et al 2021 ).…”
Section: Microbes Drive Hallmarks Of Cancermentioning
confidence: 99%
“…Pathogenic strains produce toxins, including colibactin, cytolethal distending toxin (CDT), cycle inhibiting factor, and cytotoxic necrotizing factor [ 67 ]. CDT is a genotoxin composed of CdtA, CdtB, and CdtC subunits [ 68 ], while the CdtB catalytic subunit might support carcinogenesis and host cell transformation in murine experiments [ 69 ]. The results from clinical studies showed that colibactin coded by Pks island was observed mainly in CRC patients [ 67 ].…”
Section: Dominant Bacteria-driven Mechanisms Associated With Cancer D...mentioning
confidence: 99%
“…CDT and CDTB (its active subunit) are mainly produced by Campylobacter jejuni . CDT can lead to genetic instability by inducing replicative stress in several human cells (e.g., HeLa, U2OS, and RKO) and human colorectal organoids ( Tremblay et al, 2021 ). This replicative stress leads to chromosomic aberrations by slowing DNA replication and expressing fragile sites.…”
Section: The Second Hit: Dysbiosis-associated Alterations Potentiate ...mentioning
confidence: 99%